2020
DOI: 10.1002/pro.3869
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CaMKIIα holoenzyme stability

Abstract: Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) is a Ser/Thr kinase necessary for long-term memory formation and other Ca 2+ -dependent signaling cascades such as fertilization. Here, we investigated the stability of CaMKIIα using a combination of differential scanning calorimetry (DSC), X-ray crystallography, and mass photometry (MP). The kinase domain has a low thermal stability (apparent T m = 36 C), which is slightly stabilized by ATP/MgCl 2 binding (apparent T m = 40 C) and significantly stabilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 42 publications
8
24
0
Order By: Relevance
“…1B). This hinge is more rigid (0.29 + 0.002 nm) than the Lat-Dim hinge (0.355 + 0.016 nm) consistent with previous work 9,12 or the AD-KD "clip" contact (0.292 + 0.005 nm). I used principal component analysis (PCA) to classify long-range collective motions within the tetramer.…”
Section: Resultssupporting
confidence: 89%
“…1B). This hinge is more rigid (0.29 + 0.002 nm) than the Lat-Dim hinge (0.355 + 0.016 nm) consistent with previous work 9,12 or the AD-KD "clip" contact (0.292 + 0.005 nm). I used principal component analysis (PCA) to classify long-range collective motions within the tetramer.…”
Section: Resultssupporting
confidence: 89%
“…This indicates that these hydrophobic residues shift to accommodate substrate binding, which is likely a large contribution to an observed gain in kinase domain stability upon GluN2B binding (Fig. S2e), similar to what we have previously observed with regulatory segment binding, which is mediated by L290 in the regulatory segment [36]. All effectors studied here have a leucine at the -5 position.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with this, a construct consisting of just the hub and the regulatory segment was shown to undergo spontaneous subunit exchange ( Bhattacharyya et al, 2016 ). Recent differential scanning calorimetry and mass photometry experiments have shown that while the isolated hub is very stable, the holoenzyme, especially with the linker present, is unstable and undergoes dissociation ( Torres-Ocampo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%